Representation of Social Actor in the News Reporting of Aljazeera Arabic and BBC Arabic on Gaza War Oct 7, 2023: Theo van Leeuwen’s Critical Discourse Analysis - Nasaruddin, Nasaruddin; Atikurrahman, Moh (Aqlam: Journal of Islam and Plurality, 2024)
Abstract: This article discusses the news coverage of the Gaza conflict presented in Arabic. News narratives are understood as ideological, political, non-neutral discourse practices and so on. This study is a critical discourse analysis of news from two mainstream news agencies representing the Middle East (Al-Jazeera Arabic) and the West (BBC Arabic) regarding the war that has been going on since October 7, 2023. The paradigm used in this study is socio-semantics initiated by Theo van Leeweun. News narratives, for van Leeweun, are a field for social actors to seize the public discourse stage. There are two main strategies called (a) exclusion and (b) inclusion that are always carried out by the editorial team in their journalistic work. The findings that can be concluded are that BBC Arabic, as a representation of Western society, tends to side with Israel and ignores Palestinian civilians. On the other hand, Al-Jazeera Arabic is more proportional (balanced) in telling the story of the events involving Palestine-Israel. Al-Jazeera Arabic is also more humanistic as seen from how they focus more on the weak side, namely the Gaza civilians who are the real victims of the war.Keywords: Gaza, BBC Arabic, Al-Jazeera Arabic, Critical Discourse Analysis, Theo van LeeweunAbstrak: Artikel ini membahas pemberitaan konflik Gaza yang disajikan dalam bahasa Arab. Narasi berita dipahami sebagai praktik wacana yang ideologis, politis, tidak netral dan sebagainya. Penelitian ini merupakan analisis wacana kritis (critical discourse analysis) terhadap pemberitaan yang bersumber dari dua kantor berita arus utama yang mewakili Timur Tengah (Al-Jazeera Arabic) dan Barat (BBC Arabic) seputar perang yang berlangsung sejak 7 Oktober 2023 silam. Paradigma yang diteladani dalam studi ini adalah sosio-semantik yang digagas oleh Theo van Leeweun. Narasi berita, bagi van Leeweun, adalah medan aktor-aktor sosial merebut panggung publik wacana. Terdapat dua strategi utama yang disebut (a) eksklusi dan (b) inklusi yang senantiasa dilakukan oleh redaksi dalam kerja jurnalisme mereka. Temuan yang bisa disimpulkan BBC Arabic, sebagai representasi masyarakat Barat cenderung berpihak ke Israel dan mengabaikan warga sipil Palestina. Sebaliknya, Al-Jazeera Arabic lebih proposional (berimbang) dalam mengisahkan peristiwa yang melibatkan Palestina-Israel tersebut. Al-Jazeera Arabic juga lebih humanis dilihat dari bagaimana mereka lebih menitikberatkan pada pihak yang lemah, yakni masyarkat sipil Gaza yang menjadi korban sesungguhnya dari perang tersebut.Kata Kunci: Gaza, BBC Arabic, Al-Jazeera Arabic, Analisis Wacana Kritis, Theo van Leeweun